Haemonchus contortus Infection Alters Gastrointestinal Microbial Community Composition, Protein Digestion and Amino Acid Allocations in Lambs - Xiang, Hai; Fang, Yi; Tan, Zhiliang; Zhong, Rongzhen (Frontiers in Microbiology, 2022)
The objective of this study was to investigate associations between gastrointestinal microbiota and protein metabolism of lambs infected with Haemonchus contortus. Sixteen male Ujumqin lambs (initial body weight = 32.4 ± 3.9 kg) were dewormed and randomly assigned to 2 equal groups, to be infected or not infected with H. contortus (GIN and CON, respectively). The experiment lasted 77 d. The GIN lambs had lower packed cell volume (PCV) and increased fecal egg count (FEC) after 14 d. Furthermore, in infected lambs, there were decreases in apparent digestibility of dry matter (P = 0.011), crude protein (P = 0.004) and ether extract (P = 0.007), as well as decreased ruminal pepsin (P < 0.001) and lipase (P = 0.032) activity but increased ruminal α-amylase (P = 0.004) and cellulase activity (P = 0.002), and decreased jejunal α-amylase activity (P = 0.033). In addition, infection with H. contortus decreased alpha diversity of the gastrointestinal microbial community in the rumen, abomasum and duodenum, although microbiota associated with carbohydrate and proteolytic metabolism were increased and up to 32 KEGG pathways in the duodenum were predicted to be significantly affected. In conclusion, H. contortus infection in lambs altered the gastrointestinal microbial community composition and disturbed protein digestion and allocation of absorbed amino acids. These results provided insights into consequences of H. contortus infection in lambs’ protein metabolism and could facilitate development of novel nutritional strategies to improve animal health.